Chaos synchronization in the presence of external disturbances with a novel layered control strategy. (15th November 2022) - Shafei, H R; Shafei, A M; Momeni, A
Abstract: In this study, a novel layered control system is designed to manage chaotic systems in the presence of external uncertainties and external disturbances. An optimal-robust control system with updated gains through an adaptive rule has been designed to deal with uncertainties in chaotic systems. An optimal control law based on the control Lyapunov function is integrated with an adaptive non-singular terminal sliding mode control law to robustly manage uncertain chaotic systems. The Lyapunov theory is also utilized to illustrate the asymptotic stability of the mentioned layered control strategy. In order to show the effectiveness of the proposed control scheme over the adaptive sliding mode control method, the chaos synchronization problem of two different chaotic systems has been conducted with this approach. The simulation results show that the presented scheme can manage chaotic systems against uncertainties and external disturbances robustly with less control effort as compared with the other method.